KOHESIVITAS TIM DAN EFIKASI DIRI SEBAGAI PREDIKTOR PRESTASI POLO AIR - Dimyati, Dimyati (Jurnal Penelitian Humaniora, 2015)
Abstract This research aimed to examine: (1) the relationship between cohesiveness and the achievement of the water polo team, (2) the relationship between self-efficacy and the team achievement. (3) the differences of cohesiveness degree and self-efficacy among each water polo team. The subjects of the research were water polo athletes taking part in National Games (PON) XV in the year of 2000 in Surabaya. The method and the instrument used are questionnaire method and modified Likert scale. The team cohesion questionnaire (TCQ) instrument is used to find out the team cohesiveness. The computation using regression analysis found that the value of R= 0.951 (p<0.05). It implies that there exists a positive and significant relationship between team cohesiveness as well as self-efficacy along with achievement of water polo team. Product moment analysis is carried out to seek the relationship between team cohesiveness and the team achievement resulting in the value of r=0.973, whereas the relationship between self-efficacy and the achievement of water polo team meet the value of r=0.975. based on the one-way varian analysis. The significant difference (F=19.117) of the team cohesiveness as well as self-efficacy (F=26.542) of each water polo team is revealed. Keywords: team cohesiveness, self-efficacy, achievement, water polo